Organization theory : from chester barnard to the present and beyond / edited by Oliver E. Williamson - "Williamson, Oliver E. (ed.)" (New York, 1995)
This book is made up of chapters by experts in organization theory who have addressed issues originally formulated by Chester Barnard in his seminal book, The Functions of the Executive. Each author discusses concepts introduced by Barnard, and then explores future prospects for organization theory. The authors provide many perspectives on organization theory that carry forward the work begun by Barnard. The book derives from a seminar series given at the University of California at Berkeley Business School.